Adaptive Response of Listeria monocytogenes to the Stress Factors in the Food Processing Environment - Wiktorczyk-Kapischke, Natalia; Skowron, Krzysztof; Grudlewska-Buda, Katarzyna; Wałecka-Zacharska, Ewa; Korkus, Jakub; Gospodarek-Komkowska, Eugenia (Frontiers in Microbiology, 2021)
Listeria monocytogenes are Gram-positive, facultatively anaerobic, non-spore-forming bacteria that easily adapt to changing environmental conditions. The ability to grow at a wide range of temperatures, pH, and salinity determines the presence of the pathogen in water, sewage, soil, decaying vegetation, and animal feed. L. monocytogenes is an etiological factor of listeriosis, especially dangerous for the elderly, pregnant women, and newborns. The major source of L. monocytogenes for humans is food, including fresh and smoked products. Its high prevalence in food is associated with bacterial adaptation to the food processing environment. Since the number of listeriosis cases has been progressively increasing an efficient eradication of the pathogen from the food processing environment is crucial. Understanding the mechanisms of bacterial adaptation to environmental stress will significantly contribute to developing novel, effective methods of controlling L. monocytogenes in the food industry.